A Survey of ICI Self-Cancellation Techniques for OFDM Systems (International Journal of Engineering and Computer Science, 2017)
Inter-carrier Interference (ICI) is a severe problem in orthogonal frequency division multiplexing (OFDM) systems. Any offset between the subcarrier frequencies of the transmitter and receiver ruins the orthogonality of OFDM subcarriers and introduces ICI to an OFDM system. There are various methods to mitigate the effects of ICI. In this paper various ICI self-cancellation (ICI-SC) techniques to minimize ICI are studied and reviewed. Those techniques are described in this paper and a comprehensive comparison is made of all the techniques. It is found that Weighted Conjugate Transformation technique (WCT) is better than all other conventional ICI-SC schemes.